Right hemicolectomy and anterior resection using the Versius® robotic surgical system: A technical note - Frances Dixon; Parveen Vitish-Sharma; Richard O'Hara; Anjana Singh; Robin Thomas; Achal Khanna; Barrie D. Keeler (Laparoscopic, Endoscopic and Robotic Surgery, 2022)
As robotic assisted colorectal surgery increases in prevalence new systems are entering the market, each of which requires technique modifications. In this technical note we describe technical insights and tips gained from our extensive experience of 150 colorectal resections using the Versius® system from CMR Surgical. The triad of optimal bedside unit placement, port placement, and arm configuration is described for right hemicolectomy and anterior resection.